Predictors of the Treatment Response of Spontaneous Intracranial Hypotension to an Epidural Blood Patch. Issue 18 (May 2016) - Karm, Myong-Hwan; Choi, Jae-Hyung; Kim, Doohwan; Park, Jun Young; Yun, Hye Joo; Suh, Jeong Hun
Abstract : Abstract: Spontaneous intracranial hypotension (SIH) is characterized by postural headache because of low cerebrospinal fluid (CSF) pressure. Brain magnetic resonance imaging (MRI) and radioisotope (RI) cisternography can be used to identify the site of a CSF leakage. Although autologous epidural blood patch (EBP) is a very effective treatment modality, some patients require a repeat autologous EBP. We investigated whether autologous EBP responses correlate with surrogate markers of quantitative findings. All cases of autologous EBP for SIH from January 2006 to December 2014 were enrolled. The demographic variables, number of EBPs, pain scores, RI cisternography (early visualization of bladder activity), and MRI findings (subdural fluid collections, pachymeningeal enhancement, engorgement of venous structures, pituitary hyperemia, and sagging of the brain) were reviewed. Patients with early bladder activity on RI cisternography had a tendency to need a higher number of autologous EBPs. Only sagging of the brain and no other variables showed a statistically significant negative correlation with the number of autologous EBPs. The response to autologous EBP may be related to the radiologic findings of early bladder activity on RI cisternography and sagging of the brain on MRI.